1998
DOI: 10.1017/s0014479798001021
|View full text |Cite
|
Sign up to set email alerts
|

Legume Rotation in the Moist Tropical Savanna: Managing Soil Nitrogen Dynamics and Cereal Yields in Farmers' Fields

Abstract: The contribution of root and leaf litter to soil nitrogen dynamics, nitrogen uptake and balance was evaluated under cereal–legume rotations in a tropical moist savanna soil. Two legumes, soyabean (Glycine max) and stylo (Stylosanthes hamata), and maize (Zea mays) as a control were grown in four farmers' fields of different native fertility in 1993. At the end of the season, soyabean grain and stover were harvested and stylo biomass was removed for fodder. At the beginning of the 1994 season levels of total min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 0 publications
3
18
1
Order By: Relevance
“…However, legume residues containing 81-160 kg N ha -1 were returned to the soil prior to the rice crop in their study. Our values are, however, lower than the 75 kg N ha -1 earlier reported for a similar system in which the promiscuous soybean was harvested and exported from the field but the leaf litter and roots contributed N to the soil in soybean-maize rotation systems in the NGS of Nigeria (Oikeh et al 1998).…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…However, legume residues containing 81-160 kg N ha -1 were returned to the soil prior to the rice crop in their study. Our values are, however, lower than the 75 kg N ha -1 earlier reported for a similar system in which the promiscuous soybean was harvested and exported from the field but the leaf litter and roots contributed N to the soil in soybean-maize rotation systems in the NGS of Nigeria (Oikeh et al 1998).…”
Section: Discussioncontrasting
confidence: 81%
“…IRAT 136, without N fertilizer application. The positive effect of previous soybean to the NERICA rice could be attributed to N contribution by the soybean cultivars used in the present study as reported earlier (Carsky et al 1997;Oikeh et al 1998;Vanlauwe et al 2001b) and partially due to the nitrate-sparing effect (Peoples et al 1995) resulting from the previous soybean absorbing less soil N than the previous rice crop. In addition, soybean has a large belowground biomass including nodules which release N to subsequent crop through biomass decomposition Abaidoo et al 1999Abaidoo et al , 2007.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The value of bulk density was slightly above 1.39 Mg m -3 reported for surface soil of the same Northern Guinea savanna (Oikeh et al, 1998). The slightly acidic nature of the soil, low TN and OC reflected the true characteristic of a savanna Alfisol, which was due to uptake of basic cation by plant through cultivation and, partly, to the overall removal of crop residues by farmer after harvest.…”
Section: Initial Soil Characterizationmentioning
confidence: 59%